2009
DOI: 10.1103/physrevb.79.075421
|View full text |Cite
|
Sign up to set email alerts
|

Strong deviations from Fowler-Nordheim behavior for field emission from individual SiC nanowires due to restricted bulk carrier generation

Abstract: We report here field-emission ͑FE͒ studies of individual single-crystal SiC nanowires that showed several distinct I / V regimes including strong saturation resulting in highly nonlinear Fowler-Nordheim plots. The saturation is due to the formation of a depletion layer near the nanowire ends as predicted for FE from semiconductors and appears after in situ control of the surface cleanliness. This work opens the door to improving the uniformity, stability, and photon control of mass-produced planar nanowire FE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
4
23
0
Order By: Relevance
“…Ahmed et al 21 also investigated the temperature-dependent FE properties of multiwalled CNTs and attributed the behavior to increasing enhancement factors. Choueib et al 41 reported the saturation effects in the emitter currents with temperature while observing the FE of individual single crystal SiC nanowires. Li et al 19 reported the temperature dependence of the FE characteristics of graphene film and attributed the temperature dependence to elevation of the Fermi level with temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed et al 21 also investigated the temperature-dependent FE properties of multiwalled CNTs and attributed the behavior to increasing enhancement factors. Choueib et al 41 reported the saturation effects in the emitter currents with temperature while observing the FE of individual single crystal SiC nanowires. Li et al 19 reported the temperature dependence of the FE characteristics of graphene film and attributed the temperature dependence to elevation of the Fermi level with temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the optical response of such NWs is thus important for a wider community interested in other photonic devices such as photodetectors, solar cells, etc. 10 Our previous studies on FE from nominally undoped SiC NWs, 11 and more recent studies on Si NWs, 12 revealed strong nonlinearities in the FN plots with T-dependent saturation currents as predicted by theory. 8 The drops were determined by the total energy distributions (TEDs) of the emitted electrons which, when combined with the measured total current, becomes a type of two point transport measurement.…”
mentioning
confidence: 86%
“…An experimental problem was that the emitted currents were very small (pA to sub nA) and they had to be measured at high frequency. The TEDs permit to solve this problem because the voltage drops vary as a function of laser illumination (Figure 1(a)), similar as with T. 11,14 It turns out that this differentiation has no limitation in time resolution, being similar to synchronous measurements. Note that the emitted electrons originate from the conduction band in Figure 1(a).…”
mentioning
confidence: 95%
See 2 more Smart Citations